ANALISIS STRUCTURE CONDUCT PERFORMANCE PADA PEMASARAN KOMODITAS TOMAT DI KABUPATEN GARUT - Fitri Awaliyah; Vela Rostwentivaivi (Universitas Galuh Ciamis, 2021)
Garut Regency currently has the position as the largest tomato producer in West Java. The large amount of tomato production encourages a fairly broad marketing that involves a lot of marketing actors. This study aims to determine the market structure, the behavior of marketing actors, and the performance of the tomato commodity market in Garut Regency. This research was conducted in 4 districts with the largest tomato production in Garut district, namely Cikajang, Cisurupan, Cigedug and Paisrwangi. The samples taken in this research were 40 farmers and tracked the marketing of tomatoes using the snowball sampling technique. The data analysis methods used are market concentration analysis, minimum scale efficiency analysis, descriptive qualitative analysis of market behavior, and marketing margin analysis and farmer's share. The results showed that the sales ratio of 8 large tomato traders was weakly concentrated which led to monopolistic competition. There are barriers to entry to this tomato commodity market. Market behavior shows that most marketing activities are selling, buying, transporting and utilizing price information among marketing actors. The majority of the sorting and grading activities are only carried out by collector trader and wholesaler. The greatest marketing risk management occurs in farmers and retailers. Marketing margin analysis shows that the highest marketing margin occurs when tomatoes are sold for market destinations outside the island, and the lowest marketing margin occurs when tomatoes are marketed for industrial purposes. The results of farmer's share analysis show that the highest share received by farmers is when selling tomatoes for industrial needs, this happens because of the short marketing chain and the selling price for the industry is contractually above the market price.